Phenomenal Causality and Sensory Realism. (May 2020) - Meding, Kristof; Bruijns, Sebastian A.; Schölkopf, Bernhard; Berens, Philipp; Wichmann, Felix A.
One of the most important tasks for humans is the attribution of causes and effects in all wakes of life. The first systematical study of visual perception of causality—often referred to as phenomenal causality —was done by Albert Michotte using his now well-known launching events paradigm. Launching events are the seeming collision and seeming transfer of movement between two objects—abstract, featureless stimuli ("objects") in Michotte's original experiments. Here, we study the relation between causal ratings for launching events in Michotte's setting and launching collisions in a photorealistically computer-rendered setting. We presented launching events with differing temporal gaps, the same launching processes with photorealistic billiard balls, as well as photorealistic billiard balls with realistic motion dynamics, that is, an initial rebound of the first ball after collision and a short sliding phase of the second ball due to momentum and friction. We found that providing the normal launching stimulus with realistic visuals led to lower causal ratings, but realistic visuals together with realistic motion dynamics evoked higher ratings. Two-dimensional versus three-dimensional presentation, on the other hand, did not affect phenomenal causality. We discuss our results in terms of intuitive physics as well as cue conflict.